Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
For this case we have the following polynomial:
[tex]3x^2-2x+7=0[/tex]
To solve the problem, we must complete squares.
The first step is to divide the entire expression by 3.
We have then:
[tex]\frac{3}{3}x^2-\frac{2}{3}x+\frac{7}{3}=0[/tex]
The second step is to place the constant term on the right side of the equation:
[tex] \frac{3}{3}x^2-\frac{2}{3}x=-\frac{7}{3} [/tex]
The third step is to complete the square:
[tex] \frac{3}{3}x^2-\frac{2}{3}x + (-\frac{1}{3})^2=-\frac{7}{3}+ (-\frac{1}{3})^2 [/tex]
Rewriting we have:
[tex] x^2-\frac{2}{3}x + \frac{1}{9}=-\frac{7}{3}+ \frac{1}{9} [/tex]
[tex] (x-\frac{1}{3})^2 = -\frac{20}{3} [/tex]
Answer:
By completing squares we have:
[tex] (x-\frac{1}{3})^2 = -\frac{20}{3} [/tex]
Answer:
[tex]-\dfrac{20}{9}[/tex]
Explanation:
A quadratic function is a kind of function with highest degree 2 . Standard form of the quadratic equation : tex]ax^2+bx+c=0[/tex]
Further explanation:
Consider the given quadratic equation : [tex]3x^2-2x+7=0[/tex]
First we divide both sides by 3 , we get
[tex]x^2-\dfrac{2}{3}x+\dfrac{7}{3}=0[/tex]--------(1)
Compare this equation to [tex]x^2+2ax+a^2[/tex] , we have
[tex]2a=\dfrac{-2}{3}[/tex]
[tex]\Rightarrow\ a=\dfrac{-1}{3}[/tex] [divide both sides by 2]
Now using the completing the squares method , Add and subtract [tex](\dfrac{-1}{3})^2[/tex] to the left side in (1), we get
[tex]x^2-\dfrac{2}{3}x+(\dfrac{-1}{3})^2-(\dfrac{-1}{3})^2+\dfrac{7}{3}=0[/tex]
It can be written as
[tex](x^2-2(\dfrac{1}{3})x+\dfrac{1}{3})^2)-\dfrac{1}{9}+\dfrac{7}{3}=0[/tex]
Use identity [tex]x^2-2ax+a^2=(x-a)^2[/tex], we have
[tex](x-\dfrac{1}{3})^2)+\dfrac{7(3)-1}{9}=0[/tex]
[tex](x-\dfrac{1}{3})^2)+\dfrac{20}{9}=0[/tex]
Subtract [tex]\dfrac{20}{9}[/tex] from both the sides , we get
[tex](x-\dfrac{1}{3})^2)=-\dfrac{20}{9}[/tex]
Therefore, the value of [tex](x-\dfrac{1}{3})^2)=-\dfrac{20}{9}[/tex]
Learn more :
- https://brainly.com/question/10449635 [Answered by Calculista]
- https://brainly.com/question/1596209 [Answered by AkhileshT]
Keywords :
Quadratic equation, standard form, completing squares method, Polynomial identities.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.